A quantitative comparison of tools for monitoring the abundance of crown-of-thorns starfish and coral cover - Emma Lawrence; Scott D. Foster; Samuel A. Matthews; David Williamson; Morgan S. Pratchett; Jason Doyle; Scott Bainbridge; Sven Uthicke; Peter C. Doll; Brano Kusy; Mohammad A. Armin; Mary C. Bonin (Coral Reefs, 2026)
Effective monitoring of crown-of-thorns starfish (COTS) populations and coral cover is critical for informing management of COTS outbreaks throughout their tropical Indo-Pacific range, including Australia’s Great Barrier Reef. However, existing monitoring tools such as manta tow and cull diver surveys have well-known limitations including accuracy and resource demands. This study evaluates a range of monitoring tools for assessing both COTS and coral populations. Tools that measure both COTS and coral include manta tow surveys, scooter-assisted large area diver-based (SALAD) surveys and surveys undertaken using the ReefScan towed camera platform. For COTS-only monitoring, we examine cull diver surveys and environmental DNA (eDNA) sampling. Data from side-by-side deployments on seven to ten reefs (depending on the tool) with varying COTS densities and coral cover were collected and analysed to calibrate estimates between tools. The calibration models developed will aid in integrating data from diverse sources and facilitate the translation of estimates based on one monitoring tool to another. Critically, the models provide a means of estimating COTS density (COTS per hectare) for monitoring tools that do not directly collect this measure, allowing more meaningful decision-making around ecological thresholds and enabling threshold-based management regardless of which tool collected the data. The study emphasises that each tool has specific applications for addressing knowledge gaps and informing management decisions, advocating for an integrated, multi-tool monitoring strategy that leverages the strengths of each tool to improve the overall effectiveness and efficiency of COTS and coral monitoring.

The effect of Asparagopsis oil supplementation level on tissue residues and meat quality of Merino sheep fed high- or low-quality basal diets - Charlotte Adam; Emma Doyle; Jillian Dawson; Frances Cowley; Nigel Tomkins; Lewis Kahn; James Preston; Daniel Korir Sitienei; Matthew Tom Harrison; Benjamin W.B. Holman (Small Ruminant Research, 2026)

From scientific models to decisions: exploring uncertainty communication gaps between scientists and decision-makers - Annal Dhungana; Emma E. H. Doyle; Raj Prasanna; Garry McDonald (Environment Systems and Decisions, 2025)
Effective communication of uncertainty relies on transparent exchanges between scientists and decision-makers. However, significant gaps often exist between how scientists and decision-makers perceive, understand, and communicate uncertainty. This study examines the dynamics of uncertainty communication between scientists and decision-makers, employing a reflective thematic analysis of 32 interview datasets, comprising 17 scientists and 15 decision-makers. Our results show that Scientists typically approach uncertainty through methodological rigour, employing technical vocabulary and probabilistic language, which aligns with their scientific training but often complicates comprehension for decision-makers. Conversely, decision-makers prioritise actionable insights and practical implications, requiring uncertainty to be communicated in a way that supports decision-making processes across diverse contexts. The study further highlights the need for tailored communication strategies that bridge the complexities of uncertainty with the practical needs of decision-makers, emphasising collaboration and user-focused uncertainty visualisations as pathways to enhance uncertainty communication between scientists and decision-makers for the uptake of uncertainty information into decision-making.

Dose-response of Asparagopsis extract and diet quality effects enteric methane emissions for sheep fed high-forage diets - Charlotte Adam; Frances C. Cowley; Daniel Korir Sitienei; Nigel Tomkins; Lewis Kahn; James Preston; Emma Doyle (Small Ruminant Research, 2025)

Are alpacas especially protective of lambs? An insight into alpaca guardian behaviour towards sheep using an arena preference test - Paige Matthews; Amanda K. Doughty; Christine L. Morton; Jamie Barwick; Emma Doyle; Wendy Y. Brown (Applied Animal Behaviour Science, 2023)

Postnatal maternal behaviour expression depends on lambing difficulty in Merino ewes - Amellia Redfearn; Estelle Janodet; Jody McNally; Heather Brewer; Emma Doyle; Rebecca Doyle; Sabine Schmoelzl (Theriogenology, 2023)

Rethinking communication in risk interpretation and action - Shabana Khan; Jyoti L. Mishra; Kuna-hui Elaine Lin; Emma E. H. Doyle (Natural Hazards, 2017)

Investigating the impacts of captive origin, time and vegetation on the daily activity of African lion prides - Emma J. Dunston; Jackie Abell; Rebecca E. Doyle; Jacqui Kirk; Victoria B. Hilley; Andrew Forsyth; Emma Jenkins; Dominique McAllister; Rafael Freire (Journal of Ethology, 2017)

Exploring African lion (Panthera leo) behavioural phenotypes: individual differences and correlations between sociality, boldness and behaviour - Emma J. Dunston; Jackie Abell; Rebecca E. Doyle; Megan Evershed; Rafael Freire (Journal of Ethology, 2016)

Human behaviour during and immediately following earthquake shaking: developing a methodological approach for analysing video footage - Emily Lambie; Thomas M. Wilson; David M. Johnston; Steven Jensen; Erik Brogt; Emma E. H. Doyle; Michael K. Lindell; William S. Helton (Natural Hazards, 2016)